Domestic Violence and the Victim/Offender Overlap Across the Life Course - Iratzoqui, Amaia (International journal of offender therapy and comparative criminology, 2018)
The current article examined the overlap of domestic violence across the life course, connecting childhood abuse and adolescent dating victimization to adult intimate partner victimization, and the connection between these behaviors and adult domestic violence perpetration against partners and children. Using three waves of Add Health data, the study found that childhood and adolescent domestic victimization were directly and indirectly linked to adult intimate partner victimization and that domestic violence perpetration also played a role. These findings indicate that offending must be accounted for in tracking patterns of victimization over the life course and that the overlap must more directly be reconciled in current criminal justice policy.